2014
DOI: 10.1098/rspa.2014.0331
|View full text |Cite
|
Sign up to set email alerts
|

Influence of turbulence on the wake of a marine current turbine simulator

Abstract: Marine current turbine commercial prototypes have now been deployed and arrays of multiple turbines under design. The tidal flows in which they operate are highly turbulent, but the characteristics of the inflow turbulence have not being considered in present design methods. This work considers the effects of inflow turbulence on the wake behind an actuator disc representation of a marine current turbine. Different turbulence intensities and integral length scales were generated in a large eddy simulation usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 25 publications
6
50
0
Order By: Relevance
“…On the other hand, large scale turbulence interacts directly with the body itself and the wake as a whole. Similar effects have been found using porous disc rotor simulators [10], and the interaction of turbulence scale with the wake observed using Large Eddy Simulations with actuator discs [11]. It was found that small scale turbulence reduced the velocity deficit in the wake of the actuator disc, but did not significantly affect the wake expansion or wake recovery.…”
Section: Discussion Of Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…On the other hand, large scale turbulence interacts directly with the body itself and the wake as a whole. Similar effects have been found using porous disc rotor simulators [10], and the interaction of turbulence scale with the wake observed using Large Eddy Simulations with actuator discs [11]. It was found that small scale turbulence reduced the velocity deficit in the wake of the actuator disc, but did not significantly affect the wake expansion or wake recovery.…”
Section: Discussion Of Resultssupporting
confidence: 64%
“…Previous investigations have shown how the thrust coefficient, or mean (time averaged) thrust force, of a porous disc rotor simulator can vary by over 20% in turbulent flows with different turbulence characteristics [10]. Further, numerical simulations have shown how turbulence affects the wake recovery behind an actuator disc turbine representation [11]. Studies using model turbine rotors have also shown significant variations when operated in flows with different turbulence intensities [12]- [14].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Furthermore, Singh et al [29] pointed out that wind turbines reduce the intermittency and asymmetry in the wake by breaking and deflecting the large-scale flow structures; the non-local transfer between large and small scales is strongly attenuated, resulting in the more homogenized velocity structure as compared to the base flow. Numerical simulations by Blackmore et al [30] showed that the increase in Λ u of the incoming flow might speed up the wake recovery and increase the wake span.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Several marine current power research projects are underway world-wide, commercial as well as academic. 3,4 Much work has been or is being done on scale-model experiments and numerical modeling, [5][6][7][8] and investigations have been and are being performed outside the laboratories as well. 9,10 The water flow speed at a potential marine current power site is an important factor in determining the possible energy yield from the site.…”
mentioning
confidence: 99%